2019
DOI: 10.3389/fpsyg.2019.00678
|View full text |Cite
|
Sign up to set email alerts
|

Language as a Threat: Multimodal Evaluation and Interventions for Overwhelming Linguistic Anxiety in Severe Aphasia

Abstract: Linguistic anxiety (LA) is an abnormal stress response induced by situations that require the use of verbal behavior, and it is accentuated during language testing in persons with aphasia (PWA). The presence of LA in PWA may jeopardize the interpretation of cognitive evaluations, leading to biased conclusions about the severity of the language alteration and the effectiveness of the treatments. In the present study, we report the case of a woman (Mrs. A) with severe chronic mixed transcortical aphasia due to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…It is noteworthy that anxiety has received comparatively less attention in PWA than depression[ 94 , 101 ]. Impairments in the ability to communicate is one the most significant sources of stress for PWA[ 102 , 103 ]. To date, the prevalence of anxiety among PWA is estimated to be around 44%, in contrast to the 18%-25% of stroke survivors without language disorders[ 94 , 104 , 105 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that anxiety has received comparatively less attention in PWA than depression[ 94 , 101 ]. Impairments in the ability to communicate is one the most significant sources of stress for PWA[ 102 , 103 ]. To date, the prevalence of anxiety among PWA is estimated to be around 44%, in contrast to the 18%-25% of stroke survivors without language disorders[ 94 , 104 , 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…Even in mild aphasia, language-based anxiety can interfere with task performance[ 108 ]. Indeed, stress reactivity is considerably higher during linguistic in comparison to non-linguistic tasks[ 55 , 94 , 103 ] and higher anxiety and stress responses are related to non-fluent aphasias[ 96 , 102 ]. PWA also show heightened physiological arousal and anxiety scores in general compared to stroke patients without aphasia[ 94 , 109 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, group therapy can lead to more realistic attitudes toward burdensome and severely straining situations and may help caregiving spouses with coping ( Johannsen-Horbach et al, 1999 ). Studies demonstrated that merely providing information and recommendations on cognitive impairment in reducing the stroke survivor’s family stress ( McKinney et al, 2002 ; Torres-Prioris et al, 2019 ). Pooled analysis of two individual psychoeducation programs provided by Cheng et al (2014) showed a small effect on improving family functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the language changes experienced by PWA often have sudden and long-lasting negative impacts on friendships, social engagements, quality of life, and psychological wellbeing (Engelter et al, 2006;Spaccavento et al, 2014;Mattioli, 2019). Less curiosity and less emotional stability with anxiety and depression, distress, social exclusion, and loss of autonomy are frequently reported symptoms in aphasic people (Kouwenhoven et al, 2011;Ayerbe et al, 2014;Hackett and Pickles, 2014;Feigin et al, 2015;Robinson and Jorge, 2016;Mitchell et al, 2017;Kirkevold et al, 2018;Torres-Prioris et al, 2019). In particular, regardless of the degree of language impairment, the patient tends to isolate him/herself and to have less intrinsic motivation in taking part in language rehabilitation programs since he/she feels oppressed by negative feelings (Cott et al, 2007;Woodman et al, 2014;Foley et al, 2019;Hjelle et al, 2019).…”
Section: Introductionmentioning
confidence: 99%